Characterizing rice lesion mimic mutants and identifying a mutant with broad-spectrum resistance to rice blast and bacterial blight - Yin, Zhongchao; Chen, Jun; Zeng, Lirong; Goh, Meiling; Leung, Hei; Khush, Gurdev S.; Wang, Guo-Liang (Scientific Societies, 2000)
Many plant mutants develop spontaneous lesions that resemble disease symptoms in the absence of pathogen attack. In several pathosystems, lesion mimic mutations have been shown to be involved in programmed cell death, which in some instances leads to enhanced disease resistance to multiple pathogens. We investigated the relationship between spontaneous cell death and disease resistance in rice with nine mutants with a range of lesion mimic phenotypes. All nine mutations are controlled by recessive genes and some of these mutants have stunted growth and other abnormal characteristics. The lesion mimics that appeared on the leaves of these mutants were caused by cell death as measured by trypan blue staining. Activation of six defense-related genes was observed in most of the mutants when the mimic lesions developed. Four mutants exhibited significant enhanced resistance to rice blast. One of the mutants, spl11, confers non-race-specific resistance not only to blast but also to bacterial blight. The level of resistance in the spl11 mutant to the two pathogens correlates with the defense-related gene expression and lesion development on the leaves. The results suggest that some lesion mimic mutations in rice may be involved in disease resistance, and cloning of these genes may provide a clue to developing broad-spectrum resistance to diverse pathogens.